THE IMPACT OF ANTHROPOGENIC FACTORS ON THE CHANGE IN THE NATURAL STRUCTURE OF SOIL LAYERS IN THE TERRITORY OF KARAKALPAKSTAN - Nurlanov, Abdijan Sagindikovich (SCIENCE and SOCIETY, 2026)
The article examines the technological changes in the region's soil layers resulting from irrigated agriculture, industrial and household waste, as well as the Aral Sea crisis. The impact of technogenic horizons is being assessed on soil biological activity and ecological stability.
Keywords: soils of Karakalpakstan; anthropogenic skeleton; technogenic horizons; soil degradation; salinization; Aral Sea; ecological core; technogenic layers; land reclamation; land resources